Impact of IFPRI's policy research on resource allocation and food security in Bangladesh - Babu, Suresh Chandra (International Food Policy Research Institute, 2000)
The Bangladesh Food Policy Project (BFPP), implemented during 1988-94 by IFPRI in collaboration with the Bangladesh Ministry of Food, was effective in providing research-based information to enable several policy changes in the Bangladeshi food sector. This paper is an attempt to assess the impact of IFPRI’s research in Bangladesh through the BFPP. It identifies major food policy reforms designed and implemented by the Government of Bangladesh, examines their linkages to the information generated by the food policy research, and estimates the benefits of the research to the Government of Bangladesh. Based on information gathered through interviews of more than 60 senior policymakers, donor representatives, collaborators, researchers, and training recipients, the paper draws lessons for future food policy research programs in Bangladesh and other developing countries. Among the more than 70 research outputs from IFPRI, two policy contributions stand out: the abolition of the Rural Rationing program and the implementation of the Food for Education program. A case study approach is used in this paper for documenting the costs and benefits of the impacts of these contributions.